Islamic Education Learning Evaluation Strategy in Improving the Quality of Learning in Elementary Madrasah - Hani Oktasari; Monika Lismaniar; Fitriani Fitriani; Tety Rahayu; Wardania Wardania; Ahmad Syarifuddin Zuhri (BASICA, 2025)
This study aims to analyze the learning evaluation strategy of Islamic Education in improving the quality of learning in modern Islamic Elementary Schools. The study used a qualitative approach with a field study method in six Islamic Elementary Schools in Kotabumi, North Lampung. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that first, the implementation of the learning evaluation strategy of Islamic Education has led to the use of authentic evaluation through the assessment of worship practices, religious projects, observation of attitudes, and digital media that can increase student engagement and creativity in learning. Second, supporting factors for the evaluation strategy include teacher competence, support from the principal, technological facilities, and parental involvement, while inhibiting factors include limited teacher digital skills, minimal supporting facilities, and high administrative burdens. Third, the learning evaluation strategy has positive implications for improving the quality of Islamic Education learning, especially in increasing learning motivation, learning effectiveness, and strengthening students' religious and social character. Thus, the learning evaluation strategy of Islamic Education plays an important role in creating innovative, effective, and Islamic character-oriented learning.